2017
DOI: 10.1002/dev.21525
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the medial prefrontal cortex by tyrosine hydroxylase immunoreactive fibers during adolescence in male and female rats

Abstract: Adolescence is associated with continued maturation of the cerebral cortex, particularly the medial prefrontal cortex (mPFC). We have previously documented pruning in the number of neurons, dendrites and synapses in the rat mPFC from preadolescence to adulthood, with the period of pubertal onset being particularly important. We hypothesized that dopaminergic innervation of this region, critical for executive functions, would also be influenced by pubertal onset. Here, we measured changes in the volume of tyros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 44 publications
4
35
0
Order By: Relevance
“…Histological studies have also shown striking late growth of dopaminergic terminals into the primate and rodent PFC extending from the juvenile period well into the young adult period (Kalsbeek et al 1988;Benes et al 2000;Naneix et al 2012;Willing et al 2017;Hoops et al 2018). In mice, dopaminergic boutons in the PFC show greater activity-dependent plasticity in mid adolescence compared to adulthood (Mastwal et al 2014).…”
Section: Axonal Boutons In the Pfc Across Adolescent Development: Patmentioning
confidence: 99%
“…Histological studies have also shown striking late growth of dopaminergic terminals into the primate and rodent PFC extending from the juvenile period well into the young adult period (Kalsbeek et al 1988;Benes et al 2000;Naneix et al 2012;Willing et al 2017;Hoops et al 2018). In mice, dopaminergic boutons in the PFC show greater activity-dependent plasticity in mid adolescence compared to adulthood (Mastwal et al 2014).…”
Section: Axonal Boutons In the Pfc Across Adolescent Development: Patmentioning
confidence: 99%
“…The total DBH fibers length in each lamina of spinal dorsal horn were also calculated using a semi quantitative skeleton analysis adapted from Willing et al (2017). Briefly, after an adjustment of the threshold level as abovementioned, the images were converted to binary images, skeletonized using the skeleton macro from ImageJ and evaluated in terms of number of pixels occupied by skeletons.…”
Section: Dopamine-β-hydroxylase (Dbh) Immunoreactionmentioning
confidence: 99%
“…7 The total volume of the tyrosine hydroxylase containing axons in the rat mPFC in males (a) and female (b). *p < .05 ( Willing et al, 2017 ). …”
Section: Changes Not Detectable With Mrimentioning
confidence: 97%
“…We quantified the growth of axons carrying tyrosine hydroxylase (the rate limiting step for dopamine synthesis) across adolescence with regard to both sexes and puberty. A definitive role for puberty was not apparent ( Willing et al, 2017 ) ( Fig. 7 ).…”
Section: Changes Not Detectable With Mrimentioning
confidence: 99%